The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.21037/jtd.2019.06.60
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of coronary-pulmonary artery fistulas and the effectivity of trans-catheter closure: a single center experience

Abstract: Background: Due to the low prevalence, the optimal treatment strategy of coronary-pulmonary artery fistula (CPF) remains unclear, and there are no established therapeutic guidelines available. The purpose of this study is to investigate the characteristics of CPF, and evaluate the effectivity of trans-catheter closure (TCC) for CPFs. Methods: Patients with CPFs were retrospectively reviewed and enrolled according to the inclusion criteria. The data of clinical manifestations, physical signs, electrocardiogram … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…[7][8][9][10] Small single-center studies have suggested that transcatheter CAF closure is associated with a high rate of procedural success (82-93%) and relatively low morbidity in select patients. 7,8,12 Similar rates of procedural success and complications were observed in a multicenter series. 13 In the current study, procedural success occurred at a comparable rate (89.3%).…”
Section: Procedural Characteristics and Success Ratesupporting
confidence: 66%
See 1 more Smart Citation
“…[7][8][9][10] Small single-center studies have suggested that transcatheter CAF closure is associated with a high rate of procedural success (82-93%) and relatively low morbidity in select patients. 7,8,12 Similar rates of procedural success and complications were observed in a multicenter series. 13 In the current study, procedural success occurred at a comparable rate (89.3%).…”
Section: Procedural Characteristics and Success Ratesupporting
confidence: 66%
“…Since first performed in 1983 by Reidy et al, considerable advancements in transcatheter CAF closure technique and devices have been made leading to a significant increase in procedural success . Small single‐center studies have suggested that transcatheter CAF closure is associated with a high rate of procedural success (82–93%) and relatively low morbidity in select patients . Similar rates of procedural success and complications were observed in a multicenter series .…”
Section: Discussionmentioning
confidence: 67%
“…This phenomenon is also known as "coronary blood stealing (4)." Severe coronary pulmonary fistula can even lead to acute myocardial infarction, heart failure, malignant arrhythmia and sudden death (5). Therefore, the early and accurate diagnosis of coronary artery-pulmonary fistula has important clinical significance.…”
Section: Discussionmentioning
confidence: 99%
“…A Dutch study reported that cases with proximal fistulas, fistulas with termination away from the normal coronary artery, and older individuals are ideal candidates for PTE [ 20 ]. In contrast, those with larger fistulas, multiple fistulas, associated cardiac disease requiring surgical management, failure of PTE, tortuous fistulas, and large aneurysms are ideal candidates for surgical ligation [ [21] , [22] ]. In our case, we attempted PTE for treatment of the fistula, but unfortunately the procedure was unsuccessful due to the inability to enter the distal end of the fistula, which is known to happen in up to 6% of patients [ 21 ].…”
Section: Discussionmentioning
confidence: 99%